Surgical Reconstruction and Multimodal Management of Traumatic Corneoscleral Rupture with Iris Prolapse Following Blunt High-Velocity Impact: A Comprehensive Case Analysis and Clinical Review - Dewi Dwipayanti Giri; I Putu Rustama Putra (International Medical Journal Corp. Ltd, 2026)
Introduction Ocular trauma remains a significant contributor to global monocular blindness, particularly among the young and economically productive demographic. Open globe injuries (OGI), specifically those characterized by corneoscleral rupture and uveal tissue incarceration, represent a critical ophthalmic emergency that demands immediate surgical intervention to restore anatomical integrity. This report explores the management of a Zone II rupture following a motorcycle accident, emphasizing the integration of surgical repair with systemic stabilization and advanced postoperative care. Case Illustration A 21-year-old female patient presented to the emergency department thirty minutes after a high-velocity blunt impact to the right eye during a motor vehicle accident. Clinical evaluation revealed a visual acuity of 1/300 in the affected eye, a 5 mm corneoscleral rupture involving the 9 o’clock limbal meridian, and significant iris prolapse. Preoperative laboratory findings were notable for significant elevations in hepatic transaminases, suggesting subclinical blunt trauma or skeletal muscle injury. The patient underwent urgent corneoscleral suturing, iris repositioning, and bandage contact lens application. Within seven days, the visual acuity improved to 1/60, with successful restoration of the anterior chamber. Discussion The discussion evaluates the mechanical forces involved in blunt-force globe rupture, utilizing Arlt’s theory of equatorial expansion. It further analyzes the clinical decision-making process regarding iris repositioning versus excision, the importance of prompt surgical closure within 24–48 hours to mitigate endophthalmitis risk, and the utility of the Ocular Trauma Score (OTS) as a prognostic predictor. The significance of systemic laboratory markers in the context of ocular polytrauma is also examined, alongside the pharmacological rationale for combined antimicrobial and anti-inflammatory therapy. Conclusion Timely anatomical restoration through meticulous surgical technique and aggressive prophylaxis against secondary complications are fundamental to preserving visual potential in complex OGI cases. Long-term rehabilitation remains dependent on managing secondary astigmatism and monitoring for late-onset glaucoma.